Anchorage and laps of plain surface bars in R.C. structures. (15th June 2020) - Palmisano, Fabrizio; Greco, Rita; Biasi, Marika; Tondolo, Francesco; Cairns, John
Highlights: New semi-empirical formulations for anchorage and lap strength of plain surface bars of R.C. structures are proposed. The proposed formulations are based on a reliability-based approach. Practical formulations are also proposed for the second generation of Eurocodes. The proposed formulations are compared with those of previous studies and earlier codes. Abstract: Current codes of practice, mainly devoted to new structures, do not include information and approaches relevant to old material and products. At the same time, old codes are not applicable since they are not reliability-based. The increasing need for assessment and renovation of existing constructions yields the necessity to develop new approaches for old materials and products that are consistent with the requirements of current codes. In this scenario, the aim of this article is to develop a new semi-empirical formulation for anchorage and lap strength of plain surface bars of R.C. structures that is also consistent with the reliability-based approach included in the forthcoming second generation of Eurocodes. To this aim, by using a reference test database, a novel step-by-step procedure is proposed for the statistical evaluation and optimization of the contribution of each parameter affecting anchorage and lap strength. Moreover, the probabilistic calibration of the proposed expressions is performed and equations for design anchorage and lap strength are proposed. These equations have the same format as that, for ribbed bars, included in the latest draft of the second-generation Eurocode 2. Finally, the proposed formulations are compared with those of previous studies and earlier codes.